2002
DOI: 10.1104/pp.008052
|View full text |Cite
|
Sign up to set email alerts
|

The Predicted Candidates of Arabidopsis Plastid Inner Envelope Membrane Proteins and Their Expression Profiles,

Abstract: Plastid envelope proteins from the Arabidopsis nuclear genome were predicted using computational methods. Selection criteria were: first, to find proteins with NH 2 -terminal plastid-targeting peptides from all annotated open reading frames from Arabidopsis; second, to search for proteins with membrane-spanning domains among the predicted plastidial-targeted proteins; and third, to subtract known thylakoid membrane proteins. Five hundred forty-one proteins were selected as potential candidates of the Arabidops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 62 publications
3
49
0
Order By: Relevance
“…As would be predicted for an integral protein, SAMT1 was completely solubilized by treatment with 2% Triton X-100 ( Figure 2E). The localization of SAMT1 in the chloroplast envelope membranes has been suggested previously by bioinformatic analysis (Koo and Ohlrogge, 2002) and demonstrated by proteomics (Ferro et al, 2002(Ferro et al, , 2003, supporting the localization data presented in this study. Collectively, these data demonstrate that SAMT1 is an integral membrane protein that is localized in the chloroplast envelope membranes.…”
Section: Cellular Localization Of Samt1supporting
confidence: 76%
“…As would be predicted for an integral protein, SAMT1 was completely solubilized by treatment with 2% Triton X-100 ( Figure 2E). The localization of SAMT1 in the chloroplast envelope membranes has been suggested previously by bioinformatic analysis (Koo and Ohlrogge, 2002) and demonstrated by proteomics (Ferro et al, 2002(Ferro et al, , 2003, supporting the localization data presented in this study. Collectively, these data demonstrate that SAMT1 is an integral membrane protein that is localized in the chloroplast envelope membranes.…”
Section: Cellular Localization Of Samt1supporting
confidence: 76%
“…Sequence analysis of the AtOSA1 protein with Target P (http://www.cbs.dtu.dk/services/TargetP/; Emanuelsson et al, 2000), used for proteomic analyses and theoretical predictions of protein localization (Koo and Ohlrogge, 2002;Peltier et al, 2002), revealed the presence of a 28-amino acid N-terminal chloroplast targeting presequence (Supplemental Fig. S1).…”
Section: Atosa1 Is Localized In the Chloroplastmentioning
confidence: 99%
“…6,7 Although over 3600 proteins are predicted to be targeted to plastids, the number of characterized plastid proteins represents only a small percentage of this predicted number. 4,8 Despite significant efforts to characterize chloroplasts and subfractions therein, less than one-fifth of the predicted number of plastid proteins have been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…2 The remainder of the estimated 3600 plastid proteins are nuclear encoded. 3,4 The estimated number of plastid proteins for a higher plant is based upon subcellular target prediction analyses of open reading frames from the Arabidopsis thaliana genome using organelle targeting algorithms. 5 Nuclear-encoded chloroplast proteins are transcribed from the nuclear genome, translated in the cytosol and imported into chloroplasts through the envelope membrane via an amino-terminal targeting peptide.…”
Section: Introductionmentioning
confidence: 99%